2000
DOI: 10.1007/bf03179796
|View full text |Cite
|
Sign up to set email alerts
|

The role of phytic acid in legumes: antinutrient or beneficial function?

Abstract: This review describes the present state of knowledge about phytic acid (phytate), which is often present in legume seeds. The antinutritional effects of phytic acid primarily relate to the strong chelating associated with its six reactive phosphate groups. Its ability to complex with proteins and particularly with minerals has been a subject of investigation from chemical and nutritional viewpoints. The hydrolysis of phytate into inositol and phosphates or phosphoric acid occurs as a result of phytase or nonen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(169 citation statements)
references
References 120 publications
5
153
0
4
Order By: Relevance
“…Furthermore, phytic acid acts as antinutritive agent by blocking the absorption of minerals such as Fe, Zn, and Ca. The binding results in insoluble salt with poor bioavailability of minerals (Zhou and Erdman 1995;Urbano et al 2000;Feil 2001).…”
Section: Phytic Acid and Its Sources In Foodsmentioning
confidence: 99%
“…Furthermore, phytic acid acts as antinutritive agent by blocking the absorption of minerals such as Fe, Zn, and Ca. The binding results in insoluble salt with poor bioavailability of minerals (Zhou and Erdman 1995;Urbano et al 2000;Feil 2001).…”
Section: Phytic Acid and Its Sources In Foodsmentioning
confidence: 99%
“…Metabolisme ini melibatkan chelate mineral dan menghilangkan kofaktor serta membutuhkan aktivitas enzim secara optimal akibat terbentuknya reaksi kompleks fitat-enzim. Kemampuan asam fitat yang lain adalah dapat menghambat aktivitas amilase baik secara langsung atau tidak langsung dengan chelating Ca, yang merupakan kofaktor yang diperlukan untuk amilase (Rickard and Thompson, 1997 (Deshpande and Damodaran, 1989;Urbano et al, 2000;Greiner and Konietzny, 2011).…”
Section: Struktur Dan Sifat Asam Fitatunclassified
“…It is present in most of the legumes, especially high fiber diets [65][66][67][68][69][70][71]. It has been revealed that phytic acid inhibits neoplastic growth in multiple types of cancer including breast, colon, liver, prostate, rhabdomyosarcoma and skin.…”
Section: Dietary Fibersmentioning
confidence: 99%